Gerakan Sehat Peduli Lansia Di Dusun III Desa SukaSari Kecamatan Kabawetan Kabupaten Kepahiang - Hero Pratama Inzagi; Julita Sapitri; Tassyalifah Nabila Zahra; Dwi Inka Christie; Shaqia Naura Levita; Dilen Yohana; Tita Septi Handayani (Jurnal Pengabdian Mitra Persada, 2026)
Elderly age is the final stage of human life, characterized by declining bodily functions and an increased risk of chronic diseases, one of which is hypertension. Elderly health is a critical concern due to the increasing prevalence of degenerative diseases such as hypertension and decreased physical activity with age. The Healthy Care for the Elderly Movement program aims to improve the knowledge and health of the elderly through blood pressure screenings, elderly exercise demonstrations, and healthy diet education. The activity was held on December 4, 2025, at the Village Hall of Hamlet III, Suka Sari Village, Kebawetan District, Kepahiang Regency, as part of the Community Service Program (KKN) with a total duration of 30 days. The methods used included health education, blood pressure screenings, healthy diet education, and demonstrations and practice of elderly exercise. The activity results showed an increased understanding of the elderly regarding the risks of hypertension, increased participation in physical activity, and an improved understanding of a healthy diet. The activity ran smoothly and received a positive response, indicating that this program is effective as a promotive and preventive approach to maintaining the health of the elderly